Modeling Marketing Components and Subcomponents for Increasing Cinema Customers in the Iranian Cinema Market - Talebi, Morteza; Alishiri, Bahram; Salehi Sadaghiani , Jamshid (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The primary objective of this study is to explore the marketing strategies employed within the Iranian cinema industry, focusing on the components and subcomponents that influence audience engagement and increase customer base. It aims to identify effective marketing practices and the challenges faced by professionals in the context of the Iranian cinema market. Methodology: Utilizing a mixed-methods approach, the study combines qualitative interviews with 10 marketing managers from film production and distribution companies and a quantitative survey of 250 industry professionals. The qualitative data were analyzed through thematic analysis to identify key marketing components and subcomponents. The quantitative data underwent exploratory factor analysis (EFA), calculating the coefficient of determination (R^2) and applying the Fornell-Larker criterion for assessing the constructs’ discriminant validity. Findings: The study identified four main marketing components as pivotal to the Iranian cinema industry: Audience Focus, Competition Focus, Market Orientation, and Brand Orientation. These components encompassed various subcomponents such as customer preferences, social responsibility, market segmentation, and brand awareness, each contributing to the holistic marketing strategy. The quantitative analysis validated these components and indicated a significant relationship between the identified marketing strategies and their effectiveness in increasing the cinema audience. Conclusion: The study concludes that a comprehensive understanding and implementation of audience-focused, competition-driven, market-oriented, and brand-centered marketing strategies are crucial for the success and growth of the Iranian cinema industry.